사각형 마커 검출 및 인식 시스템 개발 - 이상설(Sang-Seol Lee); 정성태(Sung-Tae Jung); 강선경(Sun-Kyung Kang) (韓國컴퓨터情報學會論文誌, 2006)
In this paper, we present a method for the detection and recognition of rectangular markers from a camera image. It converts the camera image to a binary image and extracts contours of objects in the binary image. After that. it approximates the contours to a list of line segments. It finds rectangular markers by using geometrical features which are extracted from the approximated line segments. It normalizes the shape of extracted markers into exact squares by using the warping technique. It extracts feature vectors from marker image by using principal component analysis. It then calculates the distance between feature vector of input marker image and those of standard markers. Finally, it recognizes the marker by using minimum distance method. Experimental results show that the Proposed method achieves 98% recognition rate at maximum for 50 markers and execution speed of 11.1 frames/sec for images which contains eleven markers. 본 논문에서는 카메라 영상으로부터 사각형 형태의 마커를 검출하고 인식하는 방법을 제안한다. 본 논문에서는 사각형 형태의 마커 검출을 위하여 입력 영상을 이진 영상으로 변환하고 객체들의 윤곽선을 추출한 다음에 윤곽선을 선분으로 근사화 한다. 근사화된 선분으로부터 기하학적 특징을 이용하여 사각형을 찾는다. 마커의 사각형 영역을 찾은 다음에는 워핑 기법을 이용하여 사각형 마커 영상을 정사각형 형태로 정규화한다. 마커 영상을 정규화한 다음에는 주성분 분석을 통하여 마커 영상으로부터 특징 벡터를 추출하고 표준 마커에 대한 특징 벡터와의 최소 거리법에 의해 마커의 종류를 인식한다 인식 실험 결과 마커의 종류가 50개일 때에 최대 98%의 인식률을 얻을 수 있었고 입력 영상에 11개의 마커가 있는 경우에 초당 11.1 프레임의 수행 속도를 얻을 수 있었다.